Advancement of maxillary anterior segment by distraction osteogenesis for severe maxillary retrusion in cleft lip and palate - Feng, Gao; Minlie, Yang; Zhenmin, Zhao; Xiaomei, Sun; Ningbei, Yin; Yongqian, Wang; Tao, Song; Haidong, Li; Di, Wu; Jiapeng, Yin; Yimei, Cao; Haizhou, Tong (Chinese medical journal, 2014)
Background Maxillary anterior segmental distraction osteogenesis （MASDO） is a recently used method for correction of severe maxillary retrusion in cleft lip and palate （CLP） patients.In this article,we evaluated the feasibility of MASDO using rigid external distraction （RED） and rapid orthodontic tooth movement to correct severe maxillary retrusion in CLP patients.Methods Fourteen male and five female complete CLP patients between the ages of 18 and 22 years （mean age 19.7 years） at the time of distraction,with severe maxillary retrusion,were treated with the rigid external distraction （RED） device after maxillary anterior osteotomy.Rapid orthodontic tooth movement was started one week after the MASDO.Standard profile photographic,cephalometric films were obtained preoperatively and after therapy.Sella-nasion-point A （SNA） and Sella-nasion-point B （SNB） angles were measured to reflect changes in maxillary and mandibular position,and the distance between anterior nasal spine and posterior nasal spine （ANS-PNS） was measured to represent the maxillary dental arch length.Results The SNA angle increased from an average of 74.6° （range 73.0°-78.0°）,preoperatively,to 83.4° （range 78.6°-88.0°） after the RED was removed （P ＜0.01）.All cases of severe maxillary retrusion were improved.Nine patients＇ profiles became harmonious after therapy.One patient had a bimaxillary protrusion deformity and needed further surgery.The regenerate alveolar crest and edentulous space on both segments was almost completely eliminated after rapid orthodontic tooth movement.Conclusion MASDO with the RED system and rapid orthodontic tooth movement is a successful way of correcting severe maxillary retrusion in CLP patients.